2021
DOI: 10.1002/advs.202102634
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Small Extracellular Vesicles as a FGL1/PD‐L1 Dual‐Targeting Delivery System for Alleviating Immune Rejection

Abstract: There is an urgent need for developing new immunosuppressive agents due to the toxicity of long‐term use of broad immunosuppressive agents after organ transplantation. Comprehensive sample analysis revealed dysregulation of FGL1/LAG‐3 and PD‐L1/PD‐1 immune checkpoints in allogeneic heart transplantation mice and clinical kidney transplant patients. In order to enhance these two immunosuppressive signal axes, a bioengineering strategy is developed to simultaneously display FGL1/PD‐L1 (FP) on the surface of smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Engineered EVs are obtained by genetic modification of donor cells or chemical modification of EVs for targeted delivery, increasing local concentrations at diseased sites, reducing toxicity and side effects, and maximizing therapeutic efficacy (Liang et al, 2021). Tsai HI et al modified MSCs to obtain engineered EVs expressing FGL1 and PD-L1 on the membrane surface, which could target and bind to LAG-3 and PD-1 on the surface of T cells, thereby inhibiting T cell activation, and inducing immune tolerance in a heart allograft model (Tsai et al, 2022). The multidisciplinary combination helped to broaden the research horizon, overcome the research challenges, and lay the foundation for clinical translation in the field of MSC-EVs.…”
Section: Research Hotspots and Future Trendsmentioning
confidence: 99%
“…Engineered EVs are obtained by genetic modification of donor cells or chemical modification of EVs for targeted delivery, increasing local concentrations at diseased sites, reducing toxicity and side effects, and maximizing therapeutic efficacy (Liang et al, 2021). Tsai HI et al modified MSCs to obtain engineered EVs expressing FGL1 and PD-L1 on the membrane surface, which could target and bind to LAG-3 and PD-1 on the surface of T cells, thereby inhibiting T cell activation, and inducing immune tolerance in a heart allograft model (Tsai et al, 2022). The multidisciplinary combination helped to broaden the research horizon, overcome the research challenges, and lay the foundation for clinical translation in the field of MSC-EVs.…”
Section: Research Hotspots and Future Trendsmentioning
confidence: 99%
“…For example, MSC-derived sEVs have been reported to have therapeutic effects in GvHD ( Zhou et al, 2020 ) and autoimmune diseases, including the induction of tissue regeneration ( Chen et al, 2008 ), immunosuppression, and anti-inflammatory properties ( Jin-Hee et al, 2018 ). MSC-sEVs can also be modified to display multiple immunomodulatory molecules on the membrane surface to potentiate their immunosuppressive potential ( Tsai et al, 2021 ). These favorable characteristics underscore the potential of MSC-sEVs as a unique drug delivery vehicle to treat psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hsiang-I et al found that the receptors for the negative immune regulators PD-1 and LAG-3 were significantly elevated on T lymphocytes in clinical samples from kidney transplant patients and in heart transplant model mice. Therefore, they constructed PD-L1/FGL1 double-expressing MSC-exos by lentiviral vector, and both in vitro cell experiments and in vivo animal experiments confirmed that PD-L1/FGL1 double-expressing MSC-exos had stronger resistance to organ transplantation immune rejection [ 58 ]. Baculovirus is minimally virulent, neither replicates nor integrates into the host genome and is capable of transduction with high efficiency [ 59 ].…”
Section: Technologies For Engineering Mscs and Msc-exosmentioning
confidence: 99%